Branding Image Politisi Di Media Sosial (Analisis Isi Akun Instagram @deddy_mizwar) - Hamanduna, Antonius Obed lapu (LUGAS Jurnal Komunikasi, 2023)
The victory of Barack Obama in using the internet and social media to win the presidential election attracted the attention of many politicians around the world to use the internet and social media in politics. This has also attracted the attention of politicians in Indonesia to use social media to build image and voters’ participation. One of the politicians who used social media was Deddy Mizwar, namely during his time as deputy governor and when he was a candidate for governor. This study was aimed to find out the branding image built by Deddy Mizwar on the @Deddy_Mizwar Instagram account, and how he interacted with his followers. The method used was quantitative analysis with purposive sampling. This study found that Deddy Mizwar is a leader who has serving character, competent and commendable integrity.